The Role of Head Nurse, Critical Thinking Nurse And Documentation of Integrated Patient Progress Note: Cross Sectional - Nopriyanto, Dwi; Ruminem, Ruminem; Sukmana, Mayusef; Emelia, Timmy (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The study aimed to identify the relationship between the role of head nurse and critical thinking of nurse to the documentation of integrated patient progress note. The study used a descriptive correlation design, a cross sectional approach, with a sample of 69 nurses who documented integrated patient pogress note, using cluster sampling techniques, through Pearson, Spearman, Mann Whitney and Linear Regression analyzes. There was a significant relationship between the role of head nurse (p=0.038; α=0.05) and the nurse’s critical thinking (p=0.003; α=0.05) to the documentation of integrated patient progress note. Critical thinking of nurses is the most influential factor in documenting integrated patient progress note. Here needs to be a policy, evaluation and monitoring of the nursing manager through self-development in the application the role of head nurse, critical thinking of nurse and the implementation of documentation of integrated patient progress note